2016
DOI: 10.1186/s12913-016-1723-9
|View full text |Cite
|
Sign up to set email alerts
|

Access and utilization of healthcare services in Massachusetts, United States: a qualitative study of the perspectives and experiences of Brazilian-born immigrant women

Abstract: Background: Understanding immigrants' interactions with the United States (US) healthcare system will likely make it possible to meet their healthcare needs and improve their quality of life in the US. Although challenges to accessing and utilizing healthcare in the US have been identified, there is little information specific to Brazilian-born immigrants' experiences. Brazilians comprise a fast-growing immigrant population group in the US. The purpose of this study was to explore Brazilian immigrant women's p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
2
25
0
3
Order By: Relevance
“…Findings of this study revealed that for women who relied on interpreters felt that this reliance was a barrier to their communication with their primary healthcare providers and kept them from engaging in more communication with their providers about their GWG. Similar to our previous research with immigrant women of reproductive age, women in the current study felt that not being unable to communicate directly with healthcare professionals was frustrating and that this contributed to reduced communication and interactions [ 23 ]. Our findings concur with previous research showing that although the use of a professional interpreter for encounters with patients with limited English skills improves clinical care, patients’ satisfaction and outcomes with care received are diminished [ 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Findings of this study revealed that for women who relied on interpreters felt that this reliance was a barrier to their communication with their primary healthcare providers and kept them from engaging in more communication with their providers about their GWG. Similar to our previous research with immigrant women of reproductive age, women in the current study felt that not being unable to communicate directly with healthcare professionals was frustrating and that this contributed to reduced communication and interactions [ 23 ]. Our findings concur with previous research showing that although the use of a professional interpreter for encounters with patients with limited English skills improves clinical care, patients’ satisfaction and outcomes with care received are diminished [ 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 62%
“…The present study was part of community-based, mixed-method formative research being conducted (2015–present) with Latino families (multi-ethnic Hispanics and Brazilians) living in Massachusetts (MA) and Rhode Island (RI), designed to identify and explore factors influencing the risk of obesity in the first 1000 days of a child’s life [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from the UK found that non-English-speaking Somali women experienced poorer communication with health professionals when compared to English-speaking Somalis [62]. Immigrant women with low proficiency in the host country's language living in Canada, the USA, England and Portugal also experienced barriers in communication, which limited their access to maternal care services [60,71,[74][75][76][77].…”
Section: Communicationmentioning
confidence: 99%
“…Those preferences may not be accommodated by local health care systems. A study carried out in the USA found that Brazilian women prefer to have access to labour ward admission and pain management procedures earlier than they are typically offered by local maternity care [77]. Inability to exercise those preferences caused Brazilian immigrants to perceive delayed admission during labour and delayed use of anaesthetics, which impacted negatively on their satisfaction with the care received [77].…”
Section: Expression Of Preferencesmentioning
confidence: 99%